Site‐specific specimen preparation for SIMS analysis of radioactive samples - Liu, J; Li, K; Lozano-Perez, S; Grovenor, CRM (Wiley, 2020)
Secondary Ion Mass Spectrometry is an important technique for the study of the composition of a wide range of materials because of the exceptionally high sensitivity that allows the study of trace elements and the ability to distinguish isotopes that can be used as markers for reactions and transport processes. However, when studying nuclear materials, it is often necessary to analyse highly radioactive samples, and only rather few SIMS facilities are available in active environments. In this paper, we present a methodology using focussed ion beam milling to prepare samples from radioactive specimens that are sufficiently large to undertake SIMS mapping experiments over microstructurally significant regions, but with overall activities small enough to be readily transported and analysed by a SIMS instrument in a normal laboratory environment. Radioactive samples prepared using this methodology can also be used for correlative SIMS analysis with other analytical microscopies. SIMS results showing the distributions of deuterium in oxides on in‐reactor corroded zirconium alloys are presented to demonstrate the potential of this sample preparation technique.